Ser(tão) Severino: Memórias Poéticas de João Cabral De Melo Neto (1950-1960) - Galve, Fernanda Rodrigues (2006)
The thesis deals with relations between History and Literature to reflect the being and Recife as a city. Study about the poet João Cabral de Melo Neto through his book Morte e Vida Severina , written in 1954, which is a dramatic poem that approaches the tough life of the people from the Northeast Brazil and its social and historical aspects. In his literature, João Cabral mixes the historical moment to biographical elements in order to achieve an identity as a poet, he deals with images and facts, and consequently he can t consider poetry without History. Thus, the comprehension of João Cabral poetry depends on the comprehension of the historical moment, since the text dialogs constantly with concepts as culture and space. This research analyzes the connection between History and Literature, in order to show the poetry as a reflection of time and memory. This study uses a literary composition as its main source to investigate the Pernambuco society through the 50 s. Maybe this is the way to contribute to overcoming the ever-growing gap that separates the dream-like landscapes from daily life´s